Internet filtering companies with religious affiliations in the context of Indiana public libraries - Radom, Rachel (2021)
Since the U.S. Supreme Court decided to uphold the Children’s Internet Protection Act (CIPA) in 2003, public libraries accepting federal E-rate funds have been required to install technology protection measures on computers with Internet access. Many libraries use Internet filters to fulfill this requirement. Using research by Nancy Willard, which disclosed affiliations between Internet filtering companies and religious organizations, it was found that at least 15.9% of Indiana public libraries used filters with connections to conservative religious groups in 2005. Ethical implications of this research are discussed and recommendations for balancing First Amendment rights with a financial need for CIPA compliance are included.